Clockwise extrusion of the Sichuan‒Yunnan block toward the Red River Fault in the southeastern Tibetan Plateau - Zhou, Qingyun (Frontiers in Earth Science, 2024)
The Xiaojiang Fault and the Red River Fault, which are located on the southeastern margin of the Tibetan Plateau, are the eastern and southern boundaries of the Sichuan–Yunnan Block, respectively. The relationship between these two faults is highly important for the study on the tectonic evolution and seismic risk of the southeastern margin of the Tibetan Plateau. Using the digital elevation model (DEM) data, we extracted and analyzed the maximum elevation, peak steepness index, maximum slope, and relatively flat surface of the Ailaoshan Shear Zone on the southwest side of the Red River Fault. The results revealed that the geomorphic indices result around Yuanjiang were significantly lower than those on the northern and southern sides of Yuanjiang. On the basis of lithology, climate and tectonics, it is inferred that tectonic activity is the main factor controlling landform development. On the basis of existing geophysical and geomorphic survey results in this area, a geodynamic model of this area was constructed: in the mid-Miocene, tectonic inversion of the Red River Fault occurred, and material from the Tibetan Plateau flowed into the Sichuan‒Yunnan Block around the East Himalayan Syntax. The resulting extrusion caused the Red River Fault to bend of ∼50 km; in the early Pliocene, the middle and lower crust broke through the barrier and entered the interior of the Ailaoshan Shear Zone. Because of the extrusion of the middle and lower crust, the role of the Red River Fault as the boundary has weakened.